Evaluation of Propolis and Milk Administration on Caffein-Induced Mus musculus Fetus Skeletal - Dillasamola, Dwisari; A, Almahdy; Sari, Novita Purnama; Putri, Biomechy Oktomalio; Noverial, Noverial; Diliarosta, Skunda (Pharmaceutical Sciences and Research, 2018)
Caffeine consumption by pregnant women at doses above 300 mg/day was suggested to cause skeletal damage. Propolis with high flavonoids concentration could increase the number of osteoblasts. This research aims to evaluate the effect of propolis and milk administration on fetal skeletal of caffeine-induced female mice (Mus musculus). Mice were divided into six groups: negative group, positive group of caffeine (a dose of 75 mg/kg BW), positive group of propolis (a dose of 1400 mg/kg BW), positive group of milk (200 ml), group D1 (caffeine 75 mg/kg BW and propolis 1400 mg/kg BW) and group D2 (caffeine 75 mg/kg BW and milk 200 ml). Data were processed using one-way ANOVA. The results showed that administration of propolis and milk on caffeine-induced mice during pregnancy does not affect the mice body weight, the number of fetuses and fetal weight significantly (P> 0.05). No skeletal defects detected in group D1 and D2 (observation with Alizarin solution) compared to the negative group. In conclusion, the admnistration of propolis at the dose of 1400 mg/kg BW and 200 ml of milk can repair skeletal damage caused by caffeine induction.